The role of resveratrol on rheumatoid arthritis: From bench to bedside - Sheng, Shuyan; Wang, Xinyi; Liu, Xin; Hu, Xinyang; Shao, Yubao; Wang, Gaoyuan; Mao, Deshen; Li, Conghan; Chen, Bangjie; Chen, Xiaoyu (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a systemic autoimmune disease characterized by symmetrical polyarthritis as its main clinical manifestation. Uncontrolled RA eventually leads to joint deformities and loss of function. Currently, the pathogenesis of RA remains under discussion, and RA treatment is still at the bottleneck stage. Resveratrol has long been regarded as a potential antioxidant drug for RA treatment. Currently, resveratrol is considered to exert therapeutic effects on RA by activating silent information regulator 1 (SIRT1) and its downstream pathways. There is notable crosstalk between the SIRT1 and NF-κB pathways, and these pathways, which play an essential role in the development of RA, are unexpectedly linked to the influence of resveratrol. Based on recent studies of almost all the pathways that resveratrol can affect, this review summarizes a regulatory chain of core components that cover multiple tracks. We also list the effects of resveratrol on immune cells and other subtle controls, which can help clinicians understand the known mechanism of resveratrol and better treat patients with RA.